2009
DOI: 10.1159/000265569
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus versus Wall Biological Activities in Experimental Aortic Aneurysms

Abstract: Background/Aim: The intraluminal thrombus (ILT) is considered to participate in abdominal aortic aneurysm (AAA) evolution. To assess whether this role proceeds via ILT influence on biological activity of the AAA wall, we studied the relationships between the levels of some relevant proteases and microparticles (MP) released by ILT versus wall in rat experimental AAAs. Methods and Results: Two weeks after elastase perfusion, ILT and AAA wall were incubated in cell culture medium and studies were performed on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 94 publications
3
33
0
1
Order By: Relevance
“…17 The volume of mural thrombus correlates with protease activity both in the thrombus itself and within the aneurysm wall, 18 suggesting that the bigger the thrombus, the more important its biochemical effects.…”
Section: Role Of Intra-aneurysmal Thrombus In Delayed Aneurysm Rupturementioning
confidence: 99%
“…17 The volume of mural thrombus correlates with protease activity both in the thrombus itself and within the aneurysm wall, 18 suggesting that the bigger the thrombus, the more important its biochemical effects.…”
Section: Role Of Intra-aneurysmal Thrombus In Delayed Aneurysm Rupturementioning
confidence: 99%
“…8 The secretome, proteome, or transcriptome might also be good targets for identifying biomarkers, either from whole-aorta tissue [9][10][11][12][13] or from the AAA-separated layers. 14,15 However, because AAA is a complex disease, and aneurysmal tissue is similarly complex, proteomic analyses of whole-organ AAA tissue can hide cell-specific targets. Sho et al 16 reported that analysis for cell types in an experimental rat model of AAA reveals specific cellular responses to inflammation that are not shown on whole-aorta tissue.…”
mentioning
confidence: 99%
“…The model was induced under general pentobarbital (4 mg/100 g of body weight) anesthesia by in situ intraluminal pressurized perfusion of pig pancreatic elastase (3 units, E1250 [Sigma], 1-h perfusion) within an isolated segment of the abdominal aorta. This model is characterized by a biologically active intraluminal thrombus (21,22). Imaging was performed 15 d later.…”
Section: Experimental Modelsmentioning
confidence: 99%